2018
DOI: 10.5114/hm.2018.77318
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, nutrition, and bone health

Abstract: this review aims to describe the roles that physical activity and nutrition have in bone metabolism and to examine their effects on bone in a situation of altered metabolism as a consequence of inadequate nutrition and/or excessive physical activity. referring to the recent studies and the main guidelines in the literature on athlete nutrition, the paper also focuses on essential nutrients for bone health during performance. Finally, it discusses the negative effect of some nutrients on bone mineral density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 167 publications
(98 reference statements)
0
20
0
Order By: Relevance
“…Thus, in order to better understand the issue, it would be interesting to follow a group of young gymnasts in a long-term study to see if changes could occur and to what extent they would have an impact on the self-esteem of body perception, dietary habits and osteoporosis. The latter because it is recognized that physical activity and nutrition influence bone remodeling [ 58 ], but there is a lack of information on whether the composition of the meal and the timing of consumption are important for reducing acute bone resorption in children. The results of the study suggest that the consumption of a pre-exercise meal rich in carbohydrates 90 min before the training session attenuates bone resorption in prepubertal female gymnasts with respect to a meal rich in proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in order to better understand the issue, it would be interesting to follow a group of young gymnasts in a long-term study to see if changes could occur and to what extent they would have an impact on the self-esteem of body perception, dietary habits and osteoporosis. The latter because it is recognized that physical activity and nutrition influence bone remodeling [ 58 ], but there is a lack of information on whether the composition of the meal and the timing of consumption are important for reducing acute bone resorption in children. The results of the study suggest that the consumption of a pre-exercise meal rich in carbohydrates 90 min before the training session attenuates bone resorption in prepubertal female gymnasts with respect to a meal rich in proteins.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged physical exercise at a competitive level can negatively affect bone remodeling and compromise health of the skeleton (5)(6)(7). A correct diet that respects the athlete's nutritional needs with respect to physical training regimes is therefore essential to reach puberty in good physical shape (8). The degree of formation and resorption can be assessed by measuring markers of bone resorption in the blood or in the urine (9).…”
Section: Introductionmentioning
confidence: 99%
“…An example is represented by the Mini-trampoline circuit (MTC) modified and registered by Jill Cooper, created a new discipline called SupeJump®, an fitness activity recommended for everyone (5). Draper and collaborators showed that exercise on the minitrampoline provides benefits to the anaerobic system by improving muscle tolerance to lactate (6); furthermore, involving the lower and upper muscle groups, it acts at the cardiovascular level by improving the redistribution of blood flow at the muscular level, as well as the lipid profile (5) and bone metabolism (7). It is interesting to note that anaerobic exercise especially lactacid exercise has recently been reported to have a positive effect in many conditions, including pathological conditions, cerebral aging and neurodegenerative diseases (8).…”
Section: Introductionmentioning
confidence: 99%